Deficiente físico "cadeirante": identidade e individuação - Presoto, Daniel (2005)
The objective of this study was to investigate the formation of the Individual Identity of a person who in accident virtue, becoming handicapped "cadeirante" (practitioner of wheelchair Basketball). Eight integrants of Piracicaba´s team had participated in this research. Initially eight of participants three had been selected, and after only one satisfied some criteria: to be handicapped that uses wheelchair for his locomotion, to be adult and to be Basketball practitioner. The individual identified here as JM was choose because he satisfied the selection criteria and presented a life history narrative more deepened with greater conscience of his life. The Ciampa´s Identity Metamorphosis theoretical conceptualization (1987) and Mead´s Ideas (1972) revisited by Habermas (1990) had been used as theoretical support. Finally, the subject was seen presenting several personages articulated during his life history. After analysis and data interpretation, couldn´t be possible considered him as a fully emancipated subject, but he presented some fragments of emancipation and demonstrated to be in an interesting process of individuation. It was possible to make critical to the enrollment of handicapped in sport programs, that is, questions about until point these programs contribute or not for the autonomy of subject. This reveals the necessity of quarrels that extend the question in the scope to not only enclose the sportive activity, but, to unite to psychosocial aspects that the phenomenon demands like the Identity as individuation and socialization process at the same time.